Weltanschauung Al-Qur’an: Analisis Semantik Makna ‘Ankabut - Lina Fatikasari; Ni'ma Royyin Husnaya (Canonia Religia, 2026)
This study aims to reconstruct the Weltanschauung (worldview) of the Qur'an and its relevance to the concept of tawhid through a semantic analysis of the keyword ‘ankabūt (spider) using Toshihiko Izutsu's approach. This study goes beyond the general interpretation of “weakness” to reveal a deeper ideological critique, given that existing interpretations tend to stop at physical analogies. This study is a qualitative literature study using Toshihiko Izutsu's semantic analysis method. The analysis covers the basic (lexical) meaning from classical dictionaries, the relational meaning (syntagmatic and paradigmatic) in the Qur'an, and a diachronic analysis to trace shifts in meaning. The results of the study show that: (1) The lexical meaning of ‘ankabūt is “inherently constructed fragility.” (2) Relationally, the metaphor in QS. al-’Ankabūt:41 criticizes the act of taking protectors other than Allah (awliyā’) as an illusion of protection that creates a destructive system of life, an antithesis of the ideal concept of bayt (home). (3) Diachronically, the Qur'an transforms the pre-Islamic image of physical weakness into a theological metaphor about the ontological fragility of every system that is not based on Tawhid. In conclusion, ‘ankabūt is a symbol used by the Qur'an to mean “ontological failure,” which symbolizes every man-made system of dependence as inherently fragile, deceptive, and self-destructive.